2021
DOI: 10.1371/journal.pone.0256702
|View full text |Cite
|
Sign up to set email alerts
|

Associations of fat mass and muscle function but not lean mass with cognitive impairment: The Yishun Study

Abstract: Background Sarcopenia and obesity are reportedly associated with risk of cognitive decline, and sarcopenic obesity (SO) heightens the risk, but the evidence is sparse and inconclusive. This study aimed to examine the association between SO and cognitive impairment. Methods A total of 542 community-dwelling adults aged between 21 and 90 years were recruited. All participants were assessed for body composition (dual X-ray absorptiometry), handgrip strength (HGS), gait speed (GS), and cognitive function (Repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In a longitudinal cohort study, the baseline prevalence of sarcopenic obesity was 12.9%, which is similar to our study 44 . Sarcopenia and sarcopenic obesity were both associated with dementia diagnoses in that study 44 ; on the other hand, in a different study, sarcopenic obesity was not associated with cognitive functions after adjusting for age, sex, and education 45 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a longitudinal cohort study, the baseline prevalence of sarcopenic obesity was 12.9%, which is similar to our study 44 . Sarcopenia and sarcopenic obesity were both associated with dementia diagnoses in that study 44 ; on the other hand, in a different study, sarcopenic obesity was not associated with cognitive functions after adjusting for age, sex, and education 45 …”
Section: Discussionsupporting
confidence: 86%
“…44 Sarcopenia and sarcopenic obesity were both associated with dementia diagnoses in that study 44 ; on the other hand, in a different study, sarcopenic obesity was not associated with cognitive functions after adjusting for age, sex, and education. 45 Thirty percent of the patients in the obese group had sarcopenia, and 50% had malnutrition in our study. Given that sarcopenia and malnutrition are not protected by fat, obese patients may go undiagnosed for these two conditions.…”
Section: Variablesmentioning
confidence: 48%
“…Indeed, several studies have reported that SO is associated with a significantly higher risk of CI compared with sarcopenia or obesity alone in older community‐dwelling individuals 10 . However, these associations were not observed in community‐dwelling adults according to a recent study 11 . The association between SO and CI risk may vary in different populations and need to be ascertained in MHD patients due to the lack of previous studies in this population.…”
Section: Introductionmentioning
confidence: 93%
“…Sarcopenia obesity and sarcopenia alone were significantly associated with higher risk of cognitive impairment. On the other hand, a study including 542 participants 21-90 years recruited from the Chinese community produced contrasting findings [50]. The researchers obtained body composition data using dual-energy x-ray absorptiometry (DXA) and defined obesity as the upper two quintiles of fat mass index.…”
Section: Sarcopenic Obesity and Cognitive Impairmentmentioning
confidence: 99%